Breakdown of the blood-brain barrier during tick-borne encephalitis in mice is not dependent on CD8+ T-cells. - Daniel Růžek (Public Library of Science (PLoS), 2011)
Tick-borne encephalitis (TBE) virus causes severe encephalitis with serious sequelae in humans. The disease is characterized by fever and debilitating encephalitis that can progress to chronic illness or fatal infection. In this study, changes in permeability of the blood-brain barrier (BBB) in two susceptible animal models (BALB/c, and C57Bl/6 mice) infected with TBE virus were investigated at various days after infection by measuring fluorescence in brain homogenates after intraperitoneal injection of sodium fluorescein, a compound that is normally excluded from the central nervous system. We demonstrate here that TBE virus infection, in addition to causing fatal encephalitis in mice, induces considerable breakdown of the BBB. The permeability of the BBB increased at later stages of TBE infection when high virus load was present in the brain (i.e., BBB breakdown was not necessary for TBE virus entry into the brain), and at the onset of the first severe clinical symptoms of the disease, which included neurological signs associated with sharp declines in body weight and temperature. The increased BBB permeability was in association with dramatic upregulation of proinflammatory cytokine/chemokine mRNA expression in the brain. Breakdown of the BBB was also observed in mice deficient in CD8(+) T-cells, indicating that these cells are not necessary for the increase in BBB permeability that occurs during TBE. These novel findings are highly relevant to the development of future therapies designed to control this important human infectious disease.